상악 구치부에 식립된 엔도포아 임플란트의 후향적 연구 - 김상수(Sang-Soo Kim); 안미라(Mi-Ra Ahn); 이원혁(Won-hyuk Lee); 정희승(Heui-Seung Jung); 신임희(Im-hee Shin); 손동석(Dong-Seok Sohn) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2009)
Purpose: The purpose of this retrospective report was to analyze long-term survival rate of sintered porous-surfaced dental implant (Endopore Dental Implant system, Innova Corporation, Toronto, ON, Canada). Methods: 61 partially edentulous patients were received a total of 127 Endopore dental implants in the maxilla. Of the 127 implants, 24 implants were restored with individual (ie, non-splinted) crowns, while 103 implants were splinted to other implants. Medical records and radiographs were evaluated and analyzed by the cumulative survival rate, location of implants, implants length and diameter, crown/implant ratio and whether the implant was splinted. Chi squire test was used statistically. Result: Of the 127 implants, 8 implants (6.3%) were removed and and cumulative survival rate was 93.7%. Conclusion: Endopore implants showed satisfactory results after up to 8 years function periods in the edentulous posterior maxilla. KCI Citation Count: 0